The banking system : history, evolution - structure - Lolos, Leonidas S. (Greece, Athens, 1966)
The book discusses banking system which consists of regulations and applications which undergo a gradual improvement, and which are either laid down by state.
occ 16/01/2019
Loans
Keywords: Banks and banking; Banking system; Banking system - history; Greece